Catalpol promotes hippocampal neurogenesis and synaptogenesis in rats after multiple cerebral infarctions by mitochondrial regulation: involvement of the Shh signaling pathway - Huang, Zishan; Li, Feng; Zheng, Xiaoyu; Zheng, Jiarui; Dong, Yilei; Ding, Zhao; Gou, Huanyu; Yao, Mingjiang; Liu, Jianxun (Frontiers in Pharmacology, 2024)
IntroductionIschemic stroke greatly threatens human life and health. Neuro-restoration is considered to be the critical points in reestablishing neurological function and improving the quality of life of patients. Catalpol is the main active ingredient of the Chinese herbal medicine Dihuang, which has the beneficial efficacy in traditional remedy, is closely related to the mitochondrial morphology and function. In the present study, we investigated whether catalpol has a neurorestorative effect after multiple cerebral infarctions and its underlying mechanisms.MethodsIn this study, male 8-week-old Sprague-Dawley (SD) rats were grouped according to neurological deficit scores to minimize differences between groups the second day: sham group, model group, Ginkgo biloba P.E (EGb) (Ginaton:18 mg/kg) group, model + CAT 30 mg/kg group (CAT 30), model + CAT 60 mg/kg group (CAT 60), and model + CAT 120 mg/kg group (CAT 120). From the first day to the fourteenth day after MCI, rats were given the corresponding doses of drugs by gastric administration every day(1 mL/100g), and from day 7 to day 14, all rats were injected with Brdu solution (50 mg/kg) i.p. Neuro-Function was assessed by the neurologic deficit scores. Then we observed measurement of brain atrophy and fluorescent Nissl staining. The expression of BrdU+/DCX+ cells and the BDNF concentrations were tested to observe the neuro-restoration effect. Transmission electron microscope (TEM) and Western blot (WB) were used to observed synaptogenesis. we observed the restoration of mitochondrial function by detecting the intracortical calcium and T-AOC content. Finally, we examined the protein and mRNA expression of shh signaling pathway through q-PCR and WB.ResultsCatalpol alleviated neurological deficits, reduced the degree of brain atrophy, as well as minimize pathological damage in the hippocampus and cortex. In addition, catalpol also promoted hippocampal neurogenesis and synaptogenesis by improving the mitochondrial structure and promoting mitochondrial function, as evidenced by the up-regulation of positive expression of both Recombinant Doublecortin (DCX) and 5-Bromodeoxyuridinc (BrdU), the enhancement of the Total antioxidant capacity (T-AOC), and the increase in the expression of synapse-associated proteins, Synaptophysin (SYP) and post-synaptic density-95 (PSD-95). Finally, we observed that catalpol up-regulated the expression of Sonic hedgehog (Shh) and Glioma-associated homologue-1 (GLI-1), factors related to the Shh signaling pathway.DiscussionIn conclusion, catalpol may regulate mitochondria through activation of the Shh signaling pathway and exert its role in promoting hippocampal neurogenesis and synaptogenesis.